Readings in public finance - Bagchi, Amaresh (ed.) (New Delhi, 2005)
This collection of essays on the theory and development of public finance provides a comprehensive overview of the discipline and its evolution by a stellar international cast of contributors. In a substantive introduction, Amaresh Bagchi lucidly explains the basic issues that have emerged and discusses their treatment in the existing literature. The volume is divided into five thematic sections that explore
Keywords: Finance,public